Effects of environment and metacommunity delineation on multiple dimensions of stream fish beta diversity - Stoczynski, Lauren; Scott, Mark C.; Bower, Luke; Peoples, Brandon K. (Frontiers in Ecology and Evolution, 2023)
Beta diversity represents changes in community composition among locations across a landscape. While the effects of human activities on beta diversity are becoming clearer, few studies have considered human effects on the three dimensions of beta diversity: taxonomic, functional, and phylogenetic. Including anthropogenic factors and multiple dimensions of biodiversity may explain additional variation in stream fish beta diversity, providing new insight into how metacommunities are structured within different spatial delineations. In this study, we used a 350 site stream fish abundance dataset from South Carolina, USA to quantify beta diversity explainable by spatial, natural environmental, and anthropogenic variables. We investigated three spatial delineations: (1) a single whole-state metacommunity delineated by political boundaries, (2) two metacommunities delineated by a natural geomorphic break separating uplands from lowlands, and (3) four metacommunities delineated by natural watershed boundaries. Within each metacommunity we calculated taxonomic, functional, and phylogenetic beta diversity and used variation partitioning to quantify spatial, natural environmental, and anthropogenic contributions to variations in beta diversity. We explained 25-81% of the variation in stream fish beta diversity. The importance of these factors in structuring beta diversity differed among the diversity dimensions, providing different perspectives on the factors that drive beta diversity. The effect of spatial, natural environmental, and anthropogenic factors varied among the spatial delineations, suggesting conclusions drawn from variation partitioning may depend on the spatial delineation chosen by researchers. Our study highlights the importance of considering human effects on metacommunity structure, quantifying multiple dimensions of beta diversity, and careful consideration of user-defined metacommunity boundaries in beta diversity analyses.